Methods of Achieving Good GPR Image Resolution Using Focused SAR Processing - Zych, Mariusz (International Journal of Electronics and Telecommunications, 2011)
Methods of Achieving Good GPR Image Resolution Using Focused SAR Processing The paper describes the simulation and measurement results for a ground penetrating SAR radar. The main purpose of this paper is to present the complexity of the issues relating to GPR. Permittivity of the ground determination error causes the resolution deterioration of the resulting image therefore an important task of the digital signal processing is the correct estimation of the permittivity. The article presents several methods devoted to this subject. As a simulation model of SAR system the pulse radar with LFM (Linear Frequency Modulation) signal has been applied. The aim of the experiment is to test ability of the SAR system to obtain fully focused image of the underground targets. The real data measurements took place on the 6th floor at the Faculty of Electronics and Information - Warsaw University of Technology. During measurement campaign the GPR SAR demonstrator mounted on the rails wagon has been used to generate radar motion.